Sustainable Smart Tags with Two‐Step Verification for Anticounterfeiting Triggered by the Photothermal Response of Upconverting Nanoparticles. Issue 6 (8th June 2022) - Maturi, Fernando E.; Brites, Carlos D. S.; Silva, Robson R.; Nigoghossian, Karina; Wilson, Deivy; Ferreira, Rute A. S.; Ribeiro, Sidney J. L.; Carlos, Luís D.
Abstract : Sustainable QR Codes In article number 2100227, Sidney J. L. Ribeiro, Luís D. Carlos, and co‐workers demonstrate how to design sustainable QR codes by combining recycled plastic and upconverting nanoparticles. The photothermal response of the QR codes under distinct laser irradiation power densities induces color‐tuning and temperature sensing, which are used as independent encryption layers to design a double key molecular keylock accessed by a smartphone camera.